Modeling of Synchronous Reluctance Motor and Open and Closed Loop Speed Control - Dursun, Deniz Can; Yildiz, Ahmet; Polat, Mehmet (Ieee, 2022)
Synchronous reluctance motors are electrical machines that can generate mechanical energy with the principle of reluctance torque. Synchronous reluctance motors have no windings or magnets in their rotor. Therefore, they have a cheap and robust structure. The necessity of the motor driver and the high torque ripple are the disadvantages of these motors. These motors have become a widely studied machine in the field of electrical machines with the widespread use of power electronic based motor driving methods. The driver circuit of synchronous reluctance motor needs the rotor angular position to make the necessary switching. In this study, the d-q model of this motor, which has been developed in terms of performance and has increased in application in recent years, has been studied and open and closed loop speed control has been investigated. Simulation studies have been carried out in Matlab/Simulink. The accuracy of the model has been verified with the obtained results.
21st International Symposium on INFOTEH-JAHORINA (INFOTEH) -- MAR 16-18, 2022 -- BOSNIA & HERCEG
Keywords: closed loop control; open loop control; synchronous reluctance motor; speed control